Augmentation of Mass Transfer Coefficient in Decaying Swirl Flow - Kalpana, P. (Asian Journal of Chemistry, 2011)
The enhancements in mass transfer coefficients due to the presence of helical tape promoter is presented in this paper. The variables studied are the flow rate of the electrolyte, rotational speed, Reynolds number, rotational Reynolds number and Scmidt number. It is found that the mass transfer coefficient increased with increased flow rate and also increased with increase in the rotational speed. Rotation improved the mass transfer coefficient from 5-107 %. Mass transfer coefficient in the rotation of helical tape swirl generator is enhanced from 0.5 fold to 13 fold over the mass transfer coefficient in forced convection flow.